Kinders in die erediens - M. J. Beukes (HTS Teologiese Studies/Theological Studies, 1990)
Children in public worship From a biblical and historical point of view, it is clear that the child is totally part of the church of Christ, and therefore he must assemble regularly with the congregation in public worship. From an anthropological perspective, it is clear that the child, especially in the first three phases of his life, differs so greatly from the adult, that special attention should be given to him. Consequently the liturgist should bear the child in mind in every church service. From time to time special church services should be held where he focuses on the child in the first phases of his life, that is the child between five en twelve years of age.